Supervision of Mathematics Programme in Nigerian Schools and Educational Institutions - Dr. Onoge Honmane; Sunday A. O. (International Journal on Integrated Education, 2023)
This paper discussed the concept of mathematics programme and the concept of supervision. Specifically, the paper looked at barriers to effective supervision of mathematics programme in Nigerian educational institutions. The paper adopted the used of secondary data. The secondary data were obtained from online literatures and print publications. The paper concluded Shortage of mathematics Supervisors, inadequate supervision materials, lack of transportation resources, poor funding of supervision, insecurity problems, poor motivation of mathematics Supervisors and poor training of supervisor are the barriers to effective supervision of mathematics programme in educational institutions in Nigeria. Based on tis problems identified, the paper recommended the following: government should increase the funding of instructional supervision in educational institutions across the country especially that of mathematics programme. The government should employ more professional mathematics supervisors in the ministries and agencies to improve quality of mathematics supervision. More supervisory materials should be provided for all mathematics supervisors working in the federal and state ministries and department for effective supervision of mathematics programme and the government should provide adequate transportation facilities for all the departments and agencies in charge of school supervision in the various locations across the federation.